Electrolyte, lithium ion battery and electric device

CN122931028APending Publication Date: 2026-10-16EVE ENERGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611318694.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-27
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

促进锂盐解离的极性添加剂常与成膜添加剂发生竞争吸附,而自由基捕获剂又可能干扰SEI膜的有序生长,导致常规方案难以同时实现锂盐的高效解离、高温下自由基高效去除以及致密低阻抗SEI膜的形成,尤其无法适配硅基负极的体积膨胀需求

Benefits of technology

[0027] The electrolyte provided in this application uses organic molecules containing sulfonamide groups, nitrogen- and sulfur-containing heterocyclic groups, and aromatic ring groups as the first additive. The sites of each group are separated and do not interfere with each other, and they have an outstanding synergistic effect in the electrolyte. It simultaneously achieves the three-in-one function of "promoting dissociation, resisting free radicals, and orderly SEI film formation", breaking through the bottleneck of single function of additives in traditional electrolytes. It solves a number of problems such as insufficient lithium salt dissociation, insufficient electrolyte conductivity, disordered SEI film growth, poor interface stability, capacity decay caused by free radical chain reaction at high temperature, and oxidative decomposition of electrolyte in high voltage system. It also solves the problem of antagonism between multiple additives. Through the single-molecule multifunctional integrated design, it avoids polarity conflict and film formation competition between different functional additives, and achieves synergistic improvement of high conductivity, high stability, and excellent interface. This improves the stability and electrochemical performance of lithium-ion batteries under high voltage and high temperature, while also having high oxidation stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_7
    Figure SMS_7
  • Figure SMS_8
    Figure SMS_8
Patent Text Reader

Abstract

The application belongs to the technical field of lithium ion batteries, and relates to an electrolyte, a lithium ion battery and a power utilization device.The electrolyte comprises a nonaqueous solvent, a lithium salt and a first additive; the first additive comprises an organic matter containing a sulfonamide group, a nitrogen and sulfur-containing heterocyclic group and an aromatic ring group.The electrolyte disclosed by the application adds the first additive with specific group components, integrates the sulfonamide group, the nitrogen and sulfur-containing heterocyclic group and the aromatic ring group in the same molecule, simultaneously realizes the trinity function of 'promoting dissociation-anti-radical-ordered SEI film formation', and has high oxidation stability, so that the stability and electrochemical performance of the lithium ion battery under high pressure and high temperature are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application belongs to the field of lithium-ion battery technology, and relates to an electrolyte, a lithium-ion battery, and an electrical device. Background Technology

[0002] Lithium-ion batteries, as the most mainstream electrochemical energy storage devices, have been widely used in portable electronic devices, electric vehicles, and large-scale energy storage. As lithium-ion batteries develop towards higher energy density, longer cycle life, and wider temperature range adaptability, the conductivity, high-temperature stability, and high-voltage adaptability of the electrolyte have become the core bottlenecks restricting breakthroughs in battery performance.

[0003] In existing technologies, adding functional additives to electrolytes has become a core means to improve overall performance. However, existing additive technologies generally face a fundamental contradiction: single functional additives often have unintended consequences, while multiple additive combinations are prone to antagonistic effects, making it difficult to achieve a synergistic balance of high conductivity, high stability, and excellent interface. On the one hand, there is an inherent conflict between improving ionic conductivity, suppressing high-temperature free radical chain reactions, and constructing a high-quality SEI film. Polar additives that promote lithium salt dissociation often compete with film-forming additives for adsorption, while free radical scavengers may interfere with the orderly growth of the SEI film. This makes it difficult for conventional solutions to simultaneously achieve efficient lithium salt dissociation, efficient free radical removal at high temperatures, and the formation of a dense, low-resistivity SEI film, especially failing to meet the volume expansion requirements of silicon-based anodes. On the other hand, as cathode materials develop towards higher voltages (≥4.4V), the oxidative stability of existing additives is insufficient, and multi-component composite systems suffer from polarity conflicts and film-forming competition, exacerbating interfacial side reactions and performance degradation.

[0004] Therefore, developing an electrolyte that can simultaneously promote lithium salt dissociation, capture free radicals, guide high-quality SEI film formation, and possess high oxidation stability is an urgent technical problem to be solved. Summary of the Invention

[0005] To address the shortcomings of existing technologies, the purpose of this application is to provide an electrolyte, a lithium-ion battery, and an electrical device. The electrolyte of this application incorporates a first additive with specific functional groups, integrating sulfonamide groups, nitrogen- and sulfur-containing heterocyclic groups, and aromatic ring groups into the same molecule. This simultaneously achieves a three-in-one function of "promoting dissociation, resisting free radicals, and orderly SEI film formation," while also exhibiting high oxidation stability, thereby improving the stability and electrochemical performance of the lithium-ion battery under high voltage and high temperature.

[0006] To achieve the purpose of this application, the following technical solution is adopted:

[0007] In a first aspect, this application provides an electrolyte comprising a non-aqueous solvent, a lithium salt, and a first additive;

[0008] The first additive includes organic compounds containing sulfonamide groups, nitrogen- and sulfur-containing heterocyclic groups, and aromatic ring groups.

[0009] In one embodiment of this application, the first additive contains ≥2 sulfonamide groups.

[0010] In one embodiment of this application, in the first additive, the aromatic ring group is linked to at least one of the sulfonamide groups.

[0011] In one embodiment of this application, in the first additive, the two substituted sites of the nitrogen- and sulfur-containing heterocyclic groups are independently connected to sulfonamide groups.

[0012] In one embodiment of this application, the nitrogen- and sulfur-containing heterocyclic groups in the first additive include thiadiazole groups.

[0013] In one embodiment of this application, the first additive includes any one or a combination of at least two of benzopyrene, sulfadiazine, or N-(1,3-thiazolyl-2-yl)benzenesulfonamide.

[0014] In one embodiment of this application, the mass of the first additive is 0.1wt% to 5wt% of the total mass of the electrolyte, preferably 0.5wt% to 2wt%.

[0015] In one embodiment of this application, the electrolyte further includes a second additive; the second additive includes a film-forming additive.

[0016] In one embodiment of this application, the mass of the second additive is 0.1wt% to 8wt% of the total mass of the electrolyte.

[0017] In one embodiment of this application, the electrolyte further includes a third additive, which includes a dehydrating and deacidifying additive; the dehydrating and deacidifying additive includes lithium difluorophosphate and / or trimethyl phosphate.

[0018] In one embodiment of this application, the mass of the third additive is 0.1wt% to 2wt% of the total mass of the electrolyte.

[0019] In one embodiment of this application, the electrolyte further includes a fourth additive, which includes a lithium salt dissociation promoter, and the lithium salt dissociation promoter includes lithium tetrafluoroborate.

[0020] In one embodiment of this application, the mass of the fourth additive is 0.1wt% to 1wt% of the total mass of the electrolyte.

[0021] In one embodiment of this application, the concentration of the lithium salt in the electrolyte is 0.8 mol / L to 1.5 mol / L.

[0022] In one embodiment of this application, the organic solvent includes cyclic carbonates and / or chain carbonates; the mass ratio of the cyclic carbonates to the chain carbonates is (25~40):(60~75).

[0023] In a second aspect, this application provides a lithium-ion battery, the lithium-ion battery comprising the electrolyte as described in the first aspect.

[0024] In one embodiment of this application, the positive electrode active material in the lithium-ion battery includes a high-voltage positive electrode material, wherein the operating voltage of the high-voltage positive electrode material is ≥4.4V.

[0025] Thirdly, this application also provides an electrical device comprising a lithium-ion battery as described in the second aspect.

[0026] Compared with the prior art, this application has the following advantages:

[0027] The electrolyte provided in this application uses organic molecules containing sulfonamide groups, nitrogen- and sulfur-containing heterocyclic groups, and aromatic ring groups as the first additive. The sites of each group are separated and do not interfere with each other, and they have an outstanding synergistic effect in the electrolyte. It simultaneously achieves the three-in-one function of "promoting dissociation, resisting free radicals, and orderly SEI film formation", breaking through the bottleneck of single function of additives in traditional electrolytes. It solves a number of problems such as insufficient lithium salt dissociation, insufficient electrolyte conductivity, disordered SEI film growth, poor interface stability, capacity decay caused by free radical chain reaction at high temperature, and oxidative decomposition of electrolyte in high voltage system. It also solves the problem of antagonism between multiple additives. Through the single-molecule multifunctional integrated design, it avoids polarity conflict and film formation competition between different functional additives, and achieves synergistic improvement of high conductivity, high stability, and excellent interface. This improves the stability and electrochemical performance of lithium-ion batteries under high voltage and high temperature, while also having high oxidation stability. Detailed Implementation

[0028] The technical solution of this application will be further described below through specific embodiments. Those skilled in the art should understand that the embodiments described are merely to help understand this application and should not be regarded as specific limitations on this application.

[0029] In this application, technical features or solutions described using open-ended terms such as "comprising" or "including" do not exclude additional non-conflicting elements beyond those listed unless otherwise specified. They are considered to disclose both closed-ended features or solutions consisting solely of the listed elements and open-ended features or solutions that may include additional non-conflicting elements beyond those listed. For example, if A includes a1, a2, and a3, unless otherwise specified, this means that A may consist only of a1, a2, and a3, or it may include other non-conflicting elements in addition to a1, a2, and a3. This corresponds to the disclosure of technical solutions where "A consists of a1, a2, and a3" and "A includes not only a1, a2, and a3, but also other non-conflicting elements."

[0030] The above description is only a specific embodiment of this application, but the protection scope of this application is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in this application fall within the protection and disclosure scope of this application.

[0031] In one embodiment, this application provides an electrolyte comprising a non-aqueous solvent, a lithium salt, and a first additive;

[0032] The first additive includes organic compounds containing sulfonamide groups, nitrogen- and sulfur-containing heterocyclic groups, and aromatic ring groups.

[0033] The electrolyte provided in this application uses organic molecules containing sulfonamide groups, nitrogen- and sulfur-containing heterocyclic groups, and aromatic ring groups as the first additive. The sites of each group are separated and do not interfere with each other, and they have an outstanding synergistic effect in the electrolyte. It simultaneously achieves the three-in-one function of "promoting dissociation, resisting free radicals, and orderly SEI film formation", breaking through the bottleneck of single function of additives in traditional electrolytes. It solves a number of problems such as insufficient lithium salt dissociation, insufficient electrolyte conductivity, disordered SEI film growth, poor interface stability, capacity decay caused by free radical chain reaction at high temperature, and oxidative decomposition of electrolyte in high voltage system. It also solves the problem of antagonism between multiple additives. Through the single-molecule multifunctional integrated design, it avoids polarity conflict and film formation competition between different functional additives, and achieves synergistic improvement of high conductivity, high stability, and excellent interface. This improves the stability and electrochemical performance of lithium-ion batteries under high voltage and high temperature, while also having high oxidation stability.

[0034] In the electrolyte of this application, each group in the first additive plays a role, and the synergistic cooperation of each group is required to achieve the corresponding effect. Among them, the sulfonamide group is a strongly polar group (dipole moment > 4.5D), which can significantly improve the dielectric constant of the electrolyte, break the binding of lithium salt ions, promote the efficient dissociation of lithium salt, and greatly improve the ionic conductivity of the electrolyte. At the same time, the amino group (-NH-) in the sulfonamide group can react with Li + The formation of weak coordination bonds reconstructs the lithium-ion solvation sheath, reduces the desolvation energy, and optimizes ion transport kinetics. The aromatic ring, acting as an electron conjugation center, can capture free radicals (such as •OH and •F) generated by electrolyte decomposition at high temperatures through the conjugation effect, terminating the chain reaction, delaying electrolyte oxidation and battery capacity decay. Furthermore, the conjugated structure of the aromatic ring enhances the additive's thermal stability and antioxidant properties, exhibiting a high oxidation decomposition potential (≥5.3V (vsLi / Li⁺)), making it suitable for high-voltage cathode systems. The hydrophobic properties of the aromatic ring also reduce the interaction between the electrolyte and water, inhibiting the production of HF from lithium salt hydrolysis. Meanwhile, nitrogen and sulfur-containing compounds... Heterocyclic structures possess strong adsorption properties, allowing them to preferentially adsorb and orientedly align on the negative electrode surface. This guides the orderly growth of the SEI film around an inorganic phase (such as Li2S or LiF), forming a dense, low-resistance, and high-mechanical-strength SEI film. Sulfur atoms in nitrogen- and sulfur-containing heterocyclic structures can participate in SEI film formation, enhancing the film's flexibility and ionic conductivity. Consequently, a dense, low-resistance, and high-mechanical-strength ordered SEI film can be formed at the negative electrode, suppressing interfacial side reactions. Simultaneously, the nitrogen atoms in this heterocyclic structure also coordinate with transition metal ions in the positive electrode material, inhibiting the dissolution of transition metals and protecting the structural integrity of the positive electrode.

[0035] In some embodiments, the first additive contains ≥2 sulfonamide groups, such as 2, 3, 4 or 5.

[0036] In the first additive of this application, an organic compound with a polysulfonamide group is selected, which can further enhance the solvent's ability to dissolve lithium salts, avoid the bottleneck of dissociation efficiency caused by insufficient polarity of the monosulfonamide group, and further meet the requirements of higher rates.

[0037] In some embodiments, in the first additive, the aromatic ring group is linked to at least one of the sulfonamide groups.

[0038] In this application, the aromatic ring group has a certain degree of polarizability. When directly connected to a highly polar sulfonamide group, the electron cloud of the aromatic ring further enhances the electron-withdrawing ability of the sulfonamide group through conjugation and induction effects, making it a highly efficient polar center. This highly polar center can more effectively conduct dipole-ion interactions between lithium ions in the lithium salt, weakening the electrostatic attraction between lithium ions in the lithium salt and the cathode group, thereby more efficiently dissociating the lithium salt and significantly increasing the concentration of free lithium ions in the electrolyte. Furthermore, this connection enhances the conjugation effect of the aromatic ring. When the sulfonamide group or nearby solvent molecules undergo free radical chain reactions at high temperatures, it can more efficiently capture active free radicals and stabilize them by delocalizing unpaired electrons into the entire conjugated system through the resonance effect of the aromatic ring, more thoroughly suppressing chain reactions at high temperatures and significantly improving the thermal stability of the battery. It also promotes the ordered growth of the SEI film and enhances the antioxidant capacity of the first additive to a certain extent.

[0039] In this application, aromatic ring groups include, but are not limited to, benzene ring groups, naphthyl ring groups, etc.

[0040] In some embodiments, in the first additive, the two substituted sites of the nitrogen- and sulfur-containing heterocyclic groups are each independently connected to a sulfonamide group.

[0041] In some embodiments, the nitrogen- and sulfur-containing heterocyclic groups in the first additive include thiadiazole groups.

[0042] In this application, the nitrogen- and sulfur-containing heterocyclic groups are further preferably thiadiazole groups. The thiadiazole group serves as the parent nucleus connecting the two sulfonamide groups. Its rigid planar structure provides a fixed geometric template for the molecule, inducing the formation of an ordered molecular assembly layer, thereby guiding the orderly orientation and dense growth of the SEI film. The lone pair electrons of the nitrogen and sulfur atoms on its ring can form bidentate coordination with the transition metal ions on the positive electrode surface, selectively stabilizing the high-voltage positive electrode interface and inhibiting metal dissolution and electrolyte decomposition.

[0043] In some embodiments, the first additive includes any one or a combination of at least two of benzoxopramide, sulfadiazole, or N-(1,3-thiazol-2-yl)benzenesulfonamide, preferably benzoxopramide.

[0044] In this application, benzozilamide ( (CAS: 3368-13-6) As the first additive, it is more conducive to giving full play to the synergistic effect of polysulfonamide groups, thiadiazole groups and aromatic ring groups, and solves the four major problems of lithium salt dissociation, high temperature decay, interface disorder and high voltage decomposition in one stop: Among them, the bissulfonamide group promotes lithium salt dissociation efficiently through strong polar synergistic effect; the rigid planar structure of the thiadiazole ring forms a dual-site directional adsorption on the electrode surface, guiding the formation of a dense and ordered SEI film to adapt to the volume expansion of the negative electrode; the conjugated electron trapping effect of the benzene ring combined with the free radical delocalization ability of thiadiazole jointly quenches the free radicals generated by electrolyte decomposition at high temperature; the conjugated structure of benzene ring and thiadiazole further synergistically exerts antioxidant effect, fundamentally avoiding the polar conflict and film-forming competition common in multi-component additive compounding, replacing "intermolecular antagonism" with "intramolecular synergy", and achieving the synergistic unity of high conductivity, high stability and excellent interface.

[0045] In some embodiments, the mass of the first additive is 0.1wt% to 5wt% of the total mass of the electrolyte, for example, 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, 1wt%, 1.1wt%, 1.2wt%, 1.3wt%, 1.4wt%, 1.5wt%, 1.6wt%, 1.7wt%, 1.8wt%, 1.9wt%, 2wt%, 2.3wt%, 2.5wt%, 2.8wt%, 3wt%, 3.3wt%, 3.5wt%, 3.8wt%, 4wt%, 4.3wt%, 4.5wt%, 4.8wt%, or 5wt%, preferably 0.5wt% to 2wt%.

[0046] In this application, controlling the mass of the first additive to be 0.1wt%~5wt% of the total mass of the electrolyte is more conducive to promoting lithium salt dissociation, assisting interfacial film formation, and mild free radical capture. It can improve the ion conduction and interfacial stability of the electrolyte at a low addition amount. Further limiting it to 0.5wt%~2wt% significantly improves the electrolyte ion conductivity, high temperature cycling stability, high voltage oxidation resistance, and interfacial protection effect. It can fully realize the intramolecular synergy of the disulfonamide group, thiadiazole group, and aromatic ring group, maximize the three-in-one function of "promoting dissociation-suppressing free radicals-ordered SEI film formation", and avoid the problems of increased interfacial impedance and aggravated side reactions caused by excessive additives.

[0047] In some embodiments, the electrolyte further includes a second additive; the second additive includes a film-forming additive.

[0048] It is understood that this application does not specifically limit the specific types of film-forming additives. Without departing from the overall technical concept of this application, this application applies to all types of conventional film-forming additives that are reasonably known to those skilled in the art. For example, the film-forming additives include, but are not limited to, any one or at least two combinations of vinylene carbonate (VC), vinyl sulfate (DTD), fluoroethylene carbonate (FEC), or propane carbonate lactone (PS), preferably vinylene carbonate (VC) and / or fluoroethylene carbonate (FEC).

[0049] In this application, a second additive, different from the first additive, is added to the electrolyte. This second additive works synergistically with the first additive. The film-forming additive (especially VC / FEC) provides inorganic reinforcing phases such as lithium fluoride, while the first additive guides the orderly growth of the film, further improving the mechanical strength and ionic conductivity of the SEI film.

[0050] In some embodiments, the mass of the second additive is 0.1wt% to 8wt% of the total mass of the electrolyte, for example, 0.1wt%, 0.5wt%, 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, 4.5wt%, 5wt%, 5.5wt%, 6wt%, 6.5wt%, 7wt%, 7.5wt%, or 8wt%.

[0051] This application selects an appropriate amount of film-forming additive, especially preferably 0.1wt% to 8wt%, which can better exert the synergistic effect of the first additive and the second additive.

[0052] In some embodiments, the electrolyte further includes a third additive, distinct from the first additive, which includes a dehydrating and deacidifying additive; the dehydrating and deacidifying additive includes lithium difluorophosphate and / or trimethyl phosphate.

[0053] This application selects lithium difluorophosphate and / or trimethyl phosphate as dehydration and deacidification additives as the third additive. Together with the first additive, they inhibit the hydrolysis of lithium salts and remove hydrogen fluoride from the system. They also reduce water adsorption and free radical acid production. The dual effects of the first and third additives better protect the SEI interface.

[0054] In some embodiments, the mass of the third additive is 0.1wt% to 2wt% of the total mass of the electrolyte, for example, 0.1wt%, 0.5wt%, 1wt%, 1.5wt%, or 2wt%.

[0055] In this application, 0.1wt% to 2wt% of dehydration and deacidification additives are selected. While playing their own role, they can work better together with the first additive to improve the performance of the electrolyte and battery.

[0056] In some embodiments, the electrolyte further includes a fourth additive, which includes a lithium salt dissociation promoter, specifically lithium tetrafluoroborate.

[0057] In the embodiments of this application, a fourth additive different from the first additive is introduced, especially a lithium salt dissociation additive containing lithium tetrafluoroborate, which works synergistically with the first additive to further promote lithium salt dissociation, reduce electrolyte viscosity, and jointly optimize ion transport efficiency.

[0058] In some embodiments, the mass of the fourth additive is 0.1wt% to 1wt% of the total mass of the electrolyte, for example, 0.1wt%, 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, or 1wt%.

[0059] In this application, the mass of the lithium salt dissociation promoter is controlled to be 0.1wt% to 1wt% of the total mass of the electrolyte, which can not only give full play to its own role, but also greatly achieve the synergistic effect with the first additive.

[0060] In some embodiments, the concentration of the lithium salt in the electrolyte is 0.8 mol / L to 1.5 mol / L, for example, 0.8 mol / L, 0.9 mol / L, 1 mol / L, 1.1 mol / L, 1.2 mol / L, 1.3 mol / L, 1.4 mol / L, or 1.5 mol / L.

[0061] In some embodiments, the organic solvent includes cyclic carbonates and / or chain carbonates.

[0062] In some embodiments, the mass ratio of the cyclic carbonate to the chain carbonate is (25~40):(60~75), for example, 25:75, 30:70, 35:65 or 40:60, etc.

[0063] It is understood that the organic solvent and lithium salt in the electrolyte of this application are conventional technical choices. Without violating the overall technical concept of this application, any conventional electrolyte organic solvent and lithium salt system is applicable to this application.

[0064] This application further selects a combination of organic solvents containing cyclic carbonates and chain carbonates, which balances lithium salt dissociation and ion transport efficiency.

[0065] Optionally, the cyclic carbonates include, but are not limited to, ethylene carbonate (EC) and / or propylene carbonate (PC); the chain carbonates include, but are not limited to, at least one of dimethyl carbonate (DMC), ethyl methyl carbonate (EMC) or diethyl carbonate (DEC), preferably a combination of EMC and DMC.

[0066] Optionally, the lithium salt includes, but is not limited to, lithium hexafluorophosphate (LiPF6), lithium bisfluorosulfonylimide (LiFSI), or lithium difluorooxalate borate (LiDFOB).

[0067] In one embodiment, this application does not specifically limit the preparation method of the electrolyte in the above embodiments. Without violating the overall technical concept of this application, conventional electrolyte preparation methods are applicable.

[0068] For example, but not in a limiting sense, this application provides a method for preparing the electrolyte described in the above embodiments, the preparation method comprising:

[0069] In a protective atmosphere with a water oxygen content of <1ppm, an organic solvent is mixed, and then a lithium salt is added to obtain a basic electrolyte. Then, a first additive and optional second and / or optional third and / or optional fourth additives are added to the basic electrolyte in a preset ratio, and after dissolution and mixing, the electrolyte is obtained.

[0070] Optionally, the protective atmosphere includes a nitrogen atmosphere, an argon atmosphere, or a helium atmosphere, etc.

[0071] In one embodiment, this application also provides a lithium-ion battery, the lithium-ion battery comprising the electrolyte as described in the above embodiments.

[0072] It is understood that, apart from the electrolyte specified above, the lithium-ion battery in this application has conventional technical solutions in terms of structure, raw materials and preparation process. Those skilled in the art can make adaptive selections and adjustments according to actual needs.

[0073] In some embodiments, the lithium-ion battery includes a positive electrode, a negative electrode, a separator, and an electrolyte.

[0074] This application does not impose any particular limitation on the positive electrode, as long as it achieves the purpose of this application. In some embodiments, the positive electrode sheet includes a positive current collector and a positive active material layer. The positive active material layer is disposed on one or both surfaces of the positive current collector. The aforementioned "surface" can be a portion of the surface of the positive current collector or the entire surface of the positive current collector. This application does not impose any particular limitation on the positive current collector, as long as it achieves the purpose of this application. For example, the positive current collector can contain aluminum foil or aluminum alloy foil, etc. The positive active material layer of this application contains positive active material. This application does not impose any particular limitation on the type of positive active material, as long as it achieves the purpose of this application. For example, the positive active material can contain at least one of lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium iron phosphate, lithium-rich manganese-based materials, lithium cobalt oxide, lithium manganese oxide, lithium manganese iron phosphate, or lithium titanate, etc. In this application, the positive active material can also contain non-metallic elements, which can include at least one of fluorine, phosphorus, boron, chlorine, silicon, or sulfur. These elements can further improve the stability of the positive active material. In this application, there are no particular limitations on the thickness of the positive electrode current collector and the positive electrode active material layer, as long as the purpose of this application can be achieved. For example, the thickness of the positive electrode current collector is 5 μm to 20 μm. The thickness of the single-layer positive electrode active material layer is 30 μm to 120 μm. Optionally, the positive electrode active material layer may also include at least one of a conductive agent or a binder. This application does not particularly limit the types of conductive agents and binders in the positive electrode active material layer, as long as the purpose of this application can be achieved. This application does not particularly limit the mass ratio of the positive electrode active material, conductive agent, and binder in the positive electrode active material layer; those skilled in the art can choose according to actual needs, as long as the purpose of this application can be achieved.

[0075] In some embodiments, the positive electrode active material has a mass percentage of 85wt% to 98wt% in the positive electrode active material layer, such as 80wt%, 81wt%, 82wt%, 83wt%, 84wt%, 85wt%, 86wt%, 87wt%, 88wt%, 89wt%, 90wt%, 91wt%, 92wt%, 93wt%, 94wt%, 95wt%, 96wt%, 97wt%, or 98wt%.

[0076] The separator of this application is disposed between the positive electrode and the negative electrode to separate them. This application does not impose any particular limitation on the separator, as long as it achieves the purpose of this application. For example, the separator material may include, but is not limited to, at least one of polyethylene (PE), polyolefins (PO) primarily composed of polypropylene (PP), polyester (e.g., polyethylene terephthalate (PET) film), cellulose, polyimide (PI), polyamide (PA), spandex, or aramid. The separator type may include at least one of woven membrane, nonwoven membrane, microporous membrane, composite membrane, rolled membrane, or spun membrane. This application does not impose any particular limitation on the separator thickness, as long as it achieves the purpose of this application.

[0077] This application does not impose any particular limitation on the negative electrode, as long as the purpose of this application can be achieved. In some embodiments, the negative electrode includes a negative electrode current collector and a negative electrode active material layer, the negative electrode active material layer being disposed on one or both surfaces of the negative electrode current collector. The aforementioned "surface" can be a portion of the surface of the negative electrode current collector or the entire surface of the negative electrode current collector. For example, the negative electrode current collector may contain copper foil or copper alloy foil, etc. The negative electrode active material layer of this application contains a negative electrode active material. The negative electrode active material includes at least one of artificial graphite, natural graphite, soft carbon, hard carbon, mesophase microcarbon spheres, silicon-based materials, and tin-based materials. Optionally, the negative electrode active material layer may also include at least one of conductive agent or binder. This application does not impose any particular limitation on the types of conductive agent and binder in the negative electrode active material layer, as long as the purpose of this application can be achieved. This application does not impose any particular limitation on the mass ratio of negative electrode active material, conductive agent, and binder in the negative electrode active material layer; those skilled in the art can choose according to actual needs, as long as the purpose of this application can be achieved.

[0078] In some embodiments, the negative electrode active material has a mass percentage of 80wt% to 98wt% in the negative electrode active material layer, such as 80wt%, 81wt%, 82wt%, 83wt%, 84wt%, 85wt%, 86wt%, 87wt%, 88wt%, 89wt%, 90wt%, 91wt%, 92wt%, 93wt%, 94wt%, 95wt%, 96wt%, 97wt%, or 98wt%.

[0079] In some embodiments, the negative electrode active material includes at least a silicon-based material; the electrolyte provided in this application can form a dense and low-resistance SEI film on the surface of the silicon-based material, which better suppresses the volume expansion of the silicon-based material system; this application does not have any particular limitation on the specific material of the silicon-based material, and those skilled in the art can choose according to actual needs, as long as the purpose of this application can be achieved.

[0080] In some embodiments, the silicon-based material includes at least one of silicon-carbon materials, silicon-oxygen materials, nano-silicon materials, porous silicon materials, or silicon alloy materials; the silicon content in the silicon-based material is ≥5 wt%.

[0081] As an example, the silicon-carbon material includes a composite material formed by embedding nano-silicon particles in a carbon matrix, wherein the carbon matrix includes, but is not limited to, at least one of porous carbon, graphite, hard carbon, soft carbon, or mesophase carbon microspheres; the silicon mass percentage in the silicon-carbon material is 5wt% to 50wt%, for example, 5wt%, 10wt%, 15wt%, 20wt%, 25wt%, 30wt%, 35wt%, 40wt%, 45wt%, or 50wt%.

[0082] As an example, the general chemical formula of the silicon-oxygen material is SiOx, where 0 < x < 2, such as 0.3, 0.5, 1, 1.5 or 1.8, etc.; the mass percentage of silicon in the silicon-oxygen material is 30wt% to 70wt%, such as 30wt%, 35wt%, 40wt%, 45wt%, 50wt%, 55wt%, 60wt%, 65wt% or 70wt%, etc.

[0083] As an example, the particle size range of the nano-silicon material is 10nm to 500nm, such as 10nm, 50nm, 100nm, 150nm, 200nm, 250nm, 300nm, 350nm, 400nm, 450nm or 500nm, etc.

[0084] As an example, the silicon alloy material includes an alloy material formed of silicon and metal M, wherein the metal M includes, but is not limited to, at least one of Fe, Al, Sn, Mg or Ti; the mass percentage of silicon in the silicon alloy material is 20wt% to 80wt%, for example, 30wt%, 35wt%, 40wt%, 45wt%, 50wt%, 55wt%, 60wt%, 65wt%, 70wt%, 75wt% or 80wt%, etc.

[0085] In some embodiments, the negative electrode active material includes a silicon-based material, and the silicon-based material accounts for 80wt% to 95wt% of the mass of the negative electrode active material layer, for example, 80wt%, 81wt%, 82wt%, 83wt%, 84wt%, 85wt%, 86wt%, 87wt%, 88wt%, 89wt%, 90wt%, 91wt%, 92wt%, 93wt%, or 94wt%, 95wt%, etc.

[0086] Furthermore, whether it is the conductive agent and binder of the positive electrode or the conductive agent and binder of the negative electrode, the conductive agent includes, but is not limited to, conductive carbon black and carbon nanotubes; the binder includes at least one of polytetrafluoroethylene, sodium carboxymethyl cellulose, styrene-butadiene rubber, polyvinylidene fluoride, nitrile rubber, styrene-ethylene-butene-styrene copolymer, styrene-butadiene-styrene copolymer, lithium polyacrylate, sodium polyacrylate, sodium alginate or lithium alginate; the conductive agent includes at least one of acetylene black, Ketjen black, Super-P, carbon nanotubes, carbon fibers or graphene.

[0087] In some embodiments, in addition to the positive electrode, separator, electrolyte, and negative electrode described above, the lithium-ion battery also includes a casing. The casing houses the positive electrode, negative electrode, separator, electrolyte, and other components known in batteries, which are not limited in this application. This application does not impose any particular limitation on the casing; it can be any casing known in the art, as long as it achieves the purpose of this application.

[0088] In some embodiments, the positive electrode active material in the lithium-ion battery includes a high-voltage positive electrode material with an operating voltage ≥4.4V, such as 4.4V, 4.45V, 4.5V, 4.55V, 4.6V, 4.65V, or 4.7V.

[0089] It is understood that the operating voltage described in this application is the charging cut-off voltage (i.e., the charging limit voltage), which is the highest voltage that the battery is allowed to reach during charging. The test conditions are as follows: the cathode material to be tested is assembled with lithium metal sheets into a CR2032 coin cell, the electrolyte used is the electrolyte of the corresponding embodiment, and a constant current charge-discharge test is performed at a constant temperature of 25°C. The charge-discharge current density is set to 0.1C~0.5C, the voltage test window is set according to the material type, and the charging cut-off voltage and discharging cut-off voltage during stable cycling from week 3 to week 5 are recorded. The average value is taken as the operating voltage of the cathode material. All voltage values ​​are relative to the Li / Li⁺ reference electrode.

[0090] The high-voltage cathode materials in this application include, but are not limited to, at least one of lithium cobalt oxide materials, high-nickel ternary materials, spinel nickel manganese oxide materials, lithium-rich manganese-based materials, high-voltage manganese iron phosphate materials, and layered-spinel composite cathode materials.

[0091] In some embodiments, the high-nickel ternary cathode material is a ternary layered cathode material with a nickel stoichiometry ≥ 0.8, and the general chemical formula of the high-nickel ternary cathode material can be LiNi. x Co y Mn z M 1-x-y-zO2, wherein 0.8 ≤ x < 1, 0 < y < 0.2, 0 < z < 0.2, and M includes a doping element, wherein the doping element includes at least one of Al, Zr, Mg, Ti, W, Mo, Nb, Y, La, Ce, Sr, V, Zn, Fe, or Cr.

[0092] For example, x can be 0.8, 0.83, 0.85, 0.88, 0.9, 0.93, 0.95, 0.98, or 0.99, etc.; y can be 0.05, 0.08, 0.1, 0.12, 0.15, 0.18, or 0.19, etc.; and z can be 0.05, 0.08, 0.1, 0.12, 0.15, 0.18, or 0.19, etc.

[0093] In some embodiments, the positive electrode active material includes a high-voltage positive electrode material, wherein the high-voltage positive electrode material accounts for 90wt% to 97wt% of the mass percentage of the positive electrode active material layer, for example, 90wt%, 91wt%, 92wt%, 93wt%, 94wt%, 95wt%, 96wt%, or 97wt%. In some embodiments, this application provides an electrical device comprising a lithium-ion battery as described in the above embodiments.

[0094] The numerical range described in this application includes not only the point values ​​listed above, but also any point values ​​between the above numerical ranges that are not listed. Due to space limitations and for the sake of brevity, this application will not exhaustively list the specific point values ​​included in the range.

[0095] Example 1

[0096] This embodiment provides an electrolyte comprising an organic solvent, a lithium salt, and a first additive; the organic solvent is EC, EMC, and DMC in a mass ratio of 35:40:25, the lithium salt is LiPF6, and the first additive is benzozilamide (CAS: 3368-13-6).

[0097] In the electrolyte, the first additive accounts for 1 wt% of the total mass of the electrolyte, and the organic solvent accounts for 85 wt% of the total mass of the electrolyte; the concentration of the lithium salt in the electrolyte is 1 mol / L.

[0098] The method for preparing the electrolyte includes:

[0099] In a glove box with an argon atmosphere containing less than 1 ppm of water and oxygen, polar cyclic carbonate EC was mixed with low-viscosity chain carbonates EMC and DMC in a predetermined ratio and stirred at room temperature for 30 minutes until completely homogeneous to obtain an organic solvent mixture system.

[0100] The lithium salt was slowly added to the above organic solvent mixture and stirred continuously for 60 minutes until completely dissolved to obtain the basic electrolyte.

[0101] The core additive benzoxopramide (BZTD) was added to the base electrolyte at a preset ratio and stirred at room temperature for 40 minutes until completely dissolved to obtain the electrolyte.

[0102] Example 2

[0103] The difference between this embodiment and Embodiment 1 is that in this embodiment, the mass percentage of the first additive in the electrolyte is 0.5 wt% of the total mass of the electrolyte, and the mass percentage of the adaptive regulating organic solvent is 85.5 wt%.

[0104] All other conditions remain the same as in Example 1.

[0105] Example 3

[0106] The difference between this embodiment and Embodiment 1 is that in this embodiment, the mass percentage of the first additive in the electrolyte is 2 wt% of the total mass of the electrolyte, and the mass percentage of the adaptive regulating organic solvent is 84 wt%.

[0107] All other conditions remain the same as in Example 1.

[0108] Example 4

[0109] The difference between this embodiment and Embodiment 1 is that in this embodiment, the mass percentage of the first additive in the electrolyte is 5 wt% of the total mass of the electrolyte, and the mass percentage of the adaptive regulating organic solvent is 81 wt%.

[0110] All other conditions remain the same as in Example 1.

[0111] Example 5

[0112] The difference between this embodiment and Embodiment 1 is that in this embodiment, the mass percentage of the first additive in the electrolyte is 8 wt% of the total mass of the electrolyte, and the mass percentage of the adaptive regulating organic solvent is 78 wt%.

[0113] All other conditions remain the same as in Example 1.

[0114] Example 6

[0115] The difference between this embodiment and Example 1 is that the first additive in this embodiment is sulfadiazine (…). CAS No.: 144-82-1.

[0116] All other conditions remain the same as in Example 1.

[0117] Example 7

[0118] The difference between this embodiment and Example 1 is that the first additive in this embodiment is N-(1,3-thiazolyl-2-yl)benzenesulfonamide ( CAS No.: 4411-72-7.

[0119] All other conditions remain the same as in Example 1.

[0120] Comparative Example 1

[0121] The difference between this embodiment and Example 1 is that the first additive in this embodiment is 5-methyl-1,3,4-thiadiazole-2-sulfonamide ( CAS No.: 66464-90-2.

[0122] All other conditions remain the same as in Example 1.

[0123] Comparative Example 2

[0124] The difference between this comparative example and Example 1 is that the first additive in this comparative example is 3-methyl-5-phenyl-1,2,4-thiadiazole ( CAS No.: 50483-77-7.

[0125] All other conditions remain the same as in Example 1.

[0126] Comparative Example 3

[0127] The difference between this comparative example and Example 1 is that the first additive in this comparative example is 1,3-benzenedisulfonamide (…). CAS No.: 3701-01-7.

[0128] All other conditions remain the same as in Example 1.

[0129] Comparative Example 4

[0130] The difference between this comparative example and Example 1 is that the electrolyte in this comparative example does not contain the first additive, which is the basic electrolyte, and the mass ratio of the adaptive organic solvent is adjusted to 86 wt%.

[0131] All other conditions remain the same as in Example 1.

[0132] Example 8

[0133] The difference between this embodiment and Embodiment 1 is that the electrolyte in this embodiment also includes a second additive, which is vinylene carbonate (VC). The mass percentage of the second additive is 2 wt% of the total mass of the electrolyte. Adaptively, the mass percentage of the organic solvent is adjusted to 83 wt%.

[0134] All other conditions remain the same as in Example 1.

[0135] Example 9

[0136] The difference between this embodiment and Embodiment 1 is that the electrolyte in this embodiment also includes a third additive, which is trimethyl phosphate (TMP). The mass percentage of the third additive is 1 wt% of the total mass of the electrolyte. Adaptively, the mass percentage of the organic solvent is adjusted to 84 wt%.

[0137] All other conditions remain the same as in Example 1.

[0138] Example 10

[0139] The difference between this embodiment and Embodiment 1 is that the electrolyte in this embodiment also includes a fourth additive, which is lithium tetrafluoroborate (LiBF4). The mass percentage of the fourth additive is 0.5 wt% of the total mass of the electrolyte. Adaptively, the mass percentage of the organic solvent is adjusted to 84.5 wt%.

[0140] All other conditions remain the same as in Example 1.

[0141] Application Example 1

[0142] This application example provides a lithium-ion battery, which includes a positive electrode, a negative electrode, a separator, and the electrolyte provided in Example 1.

[0143] The method for preparing the lithium-ion battery includes:

[0144] Preparation of positive electrode sheet

[0145] Ternary material NCM (LiNi) 0.8 Co 0.1 Mn 0.1 O2) positive electrode active material, binder PVDF (polyvinylidene fluoride), conductive agent SP (conductive carbon black Super-P) are mixed at a mass ratio of 96:1.8:2.2, and N-methylpyrrolidone (NMP) is added. After stirring evenly, a positive electrode slurry with a solid content of 63% is obtained. Then, the positive electrode slurry is coated onto aluminum foil through a coating process, and after drying and cold pressing, a positive electrode sheet is obtained.

[0146] (2) Preparation of negative electrode sheet

[0147] Silicon-carbon anode material (silicon content 15wt%), conductive agent SP (Super-P conductive carbon black), SWCNT (single-walled carbon nanotubes), and binder PAA (polyacrylic acid) are mixed in a mass ratio of 83.5:8:0.5:8, and deionized water is added. The mixture is stirred evenly to obtain an anode slurry with a solid content of 30%. The anode slurry is then coated onto a copper foil current collector through a coating process. After vacuum drying and cold pressing, the anode sheet is obtained.

[0148] (3) Selection of electrolyte

[0149] The electrolyte provided in Example 1.

[0150] (4) Selection of separator membrane

[0151] Polyethylene (PE) + ceramic was chosen as the separator for lithium-ion batteries.

[0152] (5) Preparation of lithium-ion batteries

[0153] The positive electrode, separator, and negative electrode are stacked in sequence, with the separator positioned between the positive and negative electrodes to provide isolation, resulting in a bare cell. The bare cell is then placed in an outer packaging shell, dried, and injected with electrolyte. After vacuum sealing, settling, formation, and shaping, a lithium-ion battery is obtained.

[0154] Application Example 2-10 and Comparison with Application Example 1-4

[0155] The difference between Application Example 2-10 and Comparative Application Example 1-4 is that the electrolytes provided in Example 2-10 and Comparative Example 1-4 are used respectively.

[0156] All other conditions remain the same as in Application Example 1.

[0157] Performance testing

[0158] The performance of the lithium-ion battery provided in the above application example was then compared with that of the application example. The test conditions were as follows: the rate performance of the battery was tested under the test conditions of a soft-pack battery, and the test was conducted at room temperature (25°C) on the LAND battery test system of Wuhan Jinno Electronics Co., Ltd. The charge and discharge voltage was limited to 2.5V~4.4V.

[0159] (1) High-temperature storage performance at 60℃

[0160] ① Standard charge and discharge: At 25℃, charge the lithium-ion battery at a constant current and constant voltage rate of 0.33C to 4.2V, let it stand for 10 minutes, then discharge the lithium-ion battery at a constant current rate of 0.33C to 2.5V, and let it stand for 10 minutes.

[0161] ② Initial performance test: The sample battery performance was tested using battery testing equipment at room temperature (25℃). Three standard charge-discharge cycles at 0.33C were performed, and the capacity after the third discharge was recorded. The initial capacity C0 was stored.

[0162] ③ High-temperature storage: At room temperature (25℃), the lithium-ion battery was charged to 4.2V at a constant current and constant voltage rate of 0.33C, left to stand for 30 minutes, and the cell thickness t1 was measured; then the cell was placed in a 60℃ oven for high-temperature storage for 7 days.

[0163] ④ Post-storage performance test: After the storage time is reached, the battery is removed from the high-temperature test chamber and left at room temperature for 2-4 hours to allow the battery temperature to return to room temperature. The cell thickness is measured and recorded as t2. The lithium-ion battery is then discharged at a constant current rate of 0.33C to 2.5V and left to stand for 10 minutes. The discharge capacity is the retention capacity C1. The battery is then subjected to 3 standard charge-discharge cycles at 0.33C, and the capacity of the third discharge is recorded as C2 after storage. The capacity recovery rate after 7 days of storage at 60℃ is calculated as C2 / C0×100%.

[0164] (2) High-temperature cycling performance

[0165] At 45°C, the lithium-ion battery was charged at a constant current and constant voltage of 1C to 4.4V, with a cutoff current of 0.05C. After resting for 10 minutes, the lithium-ion battery was discharged at a constant current of 1C to 2.5V and then rested for 10 minutes. This constitutes one charge-discharge cycle. The lithium-ion battery was subjected to 1000 charge-discharge cycles using the above method. The capacity retention rate of the lithium-ion battery after 1000 charge-discharge cycles at 1C / 1C was calculated.

[0166] The capacity retention rate (%) of a lithium-ion battery after N cycles = (discharge capacity of the Nth cycle / initial discharge capacity) × 100%, where N is the number of cycles of the lithium-ion battery.

[0167] (3) Test of transition metal deposition after high temperature cycling

[0168] After undergoing 1000 high-temperature cycles using the test method in (2), the battery cell was disassembled and the amount of transition metal (Ni+Co+Mn) deposited on the negative electrode was tested by ICP-OES. The calculation basis for the amount of transition metal deposited was the mass of the negative electrode material.

[0169] (4) Capacity retention rate at room temperature 1C / 10C discharge

[0170] The lithium-ion battery, after capacity gradation, was charged at 25℃ using a 1C rate with constant current and constant voltage to 4.2V, with a cutoff current of 0.05C; it was then allowed to stand for 10 minutes; next, the lithium-ion battery was discharged at a 1C rate with constant current to 2.5V, and its discharge capacity Q1C was recorded as the initial discharge capacity; then, the lithium-ion battery was charged at 25℃ using a 1C rate with constant current and constant voltage to 4.2V, with a cutoff current of 0.05C; it was allowed to stand for 10 minutes; then, the fully charged battery was discharged at a 10C rate with constant current to 2.5V, and its discharge capacity Q10C was recorded; the discharge capacity retention rate (%) of the lithium-ion battery at 1C / 10C rate was calculated as: discharge capacity Q10C at 10C rate / discharge capacity Q1C at 1C rate × 100%.

[0171] The data for Application Examples 1-7 and Comparative Application Examples 1-4 are shown in Table 1; the data for Application Examples 8-10 are shown in Table 2.

[0172] Table 1

[0173]

[0174] Table 2

[0175]

[0176] Combining Table 1 and Table 2, we can conclude that:

[0177] The electrolyte provided in this application incorporates a first additive with specific functional groups, integrating sulfonamide groups, nitrogen- and sulfur-containing heterocyclic groups, and aromatic ring groups into the same molecule. This simultaneously achieves a three-in-one function of "promoting dissociation, resisting free radicals, and forming an ordered SEI film," while also exhibiting high oxidation stability. This enhances the stability and electrochemical performance of lithium-ion batteries under high voltage and high temperature.

[0178] Data analysis of Examples 1-5 shows that controlling the mass of the first additive to 0.1wt%~5wt% of the total mass of the electrolyte is more conducive to promoting lithium salt dissociation, assisting interfacial film formation, and mild free radical capture. Even with a low addition amount, the electrolyte ion conduction and interfacial stability can be improved. Further limiting it to 0.5wt%~2wt% significantly improves the electrolyte ion conductivity, high-temperature cycle stability, high-voltage oxidation resistance, and interfacial protection effect. It can fully realize the intramolecular synergy of the disulfonamide group, thiadiazole group, and aromatic ring group, maximize the three-in-one function of "promoting dissociation-suppressing free radicals-ordered SEI film formation", and avoid the problems of increased interfacial impedance and aggravated side reactions caused by excessive additives. This allows the battery to achieve the optimal level in terms of high-temperature cycling, rate performance, high-voltage stability, and high-temperature storage.

[0179] Data analysis of Examples 1 and 6-7 shows that the number of sulfonamide groups and the corresponding thiadiazole groups and their connections in the organic compound of the first additive provided in this application have a significant synergistic effect. The use of benzozolamide as the first additive in this application demonstrates a significant synergistic effect, with the sulfonamide groups and their connections in the organic compound exhibiting a significant synergistic effect. Benzozolamide as the first additive in this application has significant advantages in promoting lithium salt dissociation through the strong polarity of the bissulfonamide groups, guiding ordered SEI film formation through the rigid thiadiazole core at two sites, and efficiently capturing free radicals and improving oxidation stability through the aromatic ring conjugated structure. Compared to the single sulfonamide structure (Example 6) and the thiadiazole-replaced structure (Example 7), its lithium salt dissociation efficiency, high-temperature free radical quenching ability, high-voltage oxidation resistance, interfacial film uniformity, and ability to inhibit transition metal dissolution are all significantly improved. It can perfectly adapt to high-nickel high-voltage cathode and silicon-based anode systems, comprehensively overcoming the performance bottlenecks caused by single functional groups or structural defects. Data analysis of Examples 1 and 8-10 shows that, in the electrolyte provided by this application, other types of additives can be compounded on the basis of the first additive, especially the film-forming additives, dehydration and deacidification additives and lithium salt dissociation promoters specified in this application. Not only will the problems of film-forming potential mismatch, polarity conflict and poor compatibility that are prone to occur when multiple functional additives are compounded not occur, but the synergistic effect of the additives can be effectively exerted to better improve the performance.

[0180] Analysis of the data from Example 1 and Comparative Examples 1-4 shows that the selection of functional groups in the first additive in the electrolyte provided in this application is crucial. They must be present simultaneously to achieve the three-in-one function of "promoting dissociation, resisting free radicals, and forming an ordered SEI film", while also taking into account the effect of high oxidation stability.

[0181] The above description is only a specific embodiment of this application, but the protection scope of this application is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in this application fall within the protection and disclosure scope of this application.

Claims

1. An electrolyte, characterized in that, The electrolyte comprises a non-aqueous solvent, a lithium salt, and a first additive; The first additive includes organic compounds containing sulfonamide groups, nitrogen- and sulfur-containing heterocyclic groups, and aromatic ring groups.

2. The electrolyte according to claim 1, characterized in that, In the first additive, the number of sulfonamide groups is ≥2; And / or, in the first additive, the aromatic ring group is linked to at least one of the sulfonamide groups; And / or, in the first additive, the two substituted sites of the nitrogen- and sulfur-containing heterocyclic groups are each independently connected to a sulfonamide group; And / or, in the first additive, the nitrogen- and sulfur-containing heterocyclic groups include thiadiazole groups.

3. The electrolyte according to claim 1 or 2, characterized in that, The first additive includes any one or a combination of at least two of benzopyrene, sulfadiazine, or N-(1,3-thiazol-2-yl)benzenesulfonamide; And / or, the mass of the first additive is 0.1wt% to 5wt% of the total mass of the electrolyte, preferably 0.5wt% to 2wt%.

4. The electrolyte according to claim 1, characterized in that, The electrolyte further includes a second additive; the second additive includes a film-forming additive. The mass of the second additive is 0.1wt% to 8wt% of the total mass of the electrolyte.

5. The electrolyte according to claim 1, characterized in that, The electrolyte also includes a third additive, which includes a dehydrating and deacidifying additive; the dehydrating and deacidifying additive includes lithium difluorophosphate and / or trimethyl phosphate. The mass of the third additive is 0.1wt% to 2wt% of the total mass of the electrolyte.

6. The electrolyte according to claim 1, characterized in that, The electrolyte further includes a fourth additive, which includes a lithium salt dissociation promoter, which includes lithium tetrafluoroborate. The mass of the fourth additive is 0.1wt% to 1wt% of the total mass of the electrolyte.

7. The electrolyte according to claim 1, characterized in that, The concentration of the lithium salt in the electrolyte is 0.8 mol / L to 1.5 mol / L; And / or, the organic solvent includes cyclic carbonates and / or chain carbonates; the mass ratio of the cyclic carbonates to the chain carbonates is (25~40):(60~75).

8. A lithium-ion battery, characterized in that, The lithium-ion battery includes the electrolyte as described in any one of claims 1-7.

9. The lithium-ion battery according to claim 8, characterized in that, The positive electrode active material in the lithium-ion battery includes a high-voltage positive electrode material, wherein the operating voltage of the high-voltage positive electrode material is ≥4.4V.

10. An electrical appliance, characterized in that, The electrical device includes a lithium-ion battery as described in claim 8 or 9.